Transcatheter aortic valve replacement using the SAPIEN 3 valve versus surgical aortic valve replacement using the rapid deployment INTUITY valve: Midterm outcomes. Issue 2 (2nd January 2021) - Useini, Dritan; Beluli, Blerta; Christ, Hildegard; Schlömicher, Markus; Ewais, Elias; Haldenwang, Peter; Patsalis, Polykarpos; Moustafine, Vadim; Bechtel, Matthias; Strauch, Justus
Abstract: Objectives: Little data have been published on the midterm effect of transapical/transfemoral‐transcatheter aortic valve replacement (TA‐/TF‐TAVR) using the Edwards SAPIEN 3 valve (S3). We aimed to compare the outcomes after TA‐/TF‐TAVR utilizing the S3 (TA‐/TF‐S3) valve with those after surgical aortic valve replacement utilizing the rapid deployment Edwards INTUITY valve (RD‐SAVR). Methods: Between March 2012 and April 2018, 122 patients with aortic stenosis underwent TA‐S3, 77 patients underwent TF‐S3 and 182 patients underwent RD‐SAVR through partial sternotomy at our institution. We conducted clinical and echocardiographic midterm follow‐ups. The primary outcomes of the study were the incidence of new pacemakers permanent pacemaker implantation (PPI), the occurrence of paravalvular leakage (PVL) and the hemodynamic performance of the valves. Results: All study groups were at intermediate surgical risk. The 30‐day all‐cause mortality and stroke rates in the TA‐S3, TF‐S3, and RD‐SAVR groups were 4.1% and 1.6%, 3.9% and 2.6%, and 3.8% and 2.2%, respectively. The RD‐SAVR group had significantly smaller PVL and PPI rates than did the TA‐/TF‐S3 group ( p < .0001). At the discharge, the one‐year postprocedure mean gradients were 9 ± 5.1/10 ± 4.5 mmHg, 11 ± 4.1/12 ± 3.8 mmHg, and 10.1 ± 4.3/10.4 ± 2.6 mmHg in the TA‐S3, TF‐S3, and RD‐SAVR groups, respectively. Midterm valve thrombosis, Re‐TAVR/SVAR were low and similar among the study groups, whereas endocarditis was higher in the TAVR group. Conclusion: RD‐SAVR was superior to TA‐/TF‐S3 in the PVL and PPI rates. We observed similar early outcomes and valve hemodynamics. The endocarditis was higher in the TAVR group.